1992
DOI: 10.4269/ajtmh.1992.46.137
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Intestinal Parasitism on Lactose Absorption in Well-Nourished African Children

Abstract: Hydrogen breath tests were performed in Gabon (Central Africa) after a loading dose of lactose in 67 well-nourished African children (50 with intestinal parasites and 17 unparasitized) and in 18 unparasitized young adults. All had normal nutritional status, and none had diarrhea or digestive symptoms. Parasites that were found included Ascaris lumbricoides in 76% of the parasitized children, Trichuris trichiura in 58%, Giardia in 24%, Entamoeba histolytica in 20%, Schistosoma intercalatum in 16%, and Necator A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 0 publications
1
14
0
1
Order By: Relevance
“…Similar results were found by Gendrel and others, who reported that asymptomatic giardiasis does not increase the frequency of lactose intolerance in well-nourished children. 4 Furthermore, Tolboom and others 27 found that lactose malabsorption does not correlate with the presence of giardiasis, but milk intolerance manifested as diarrhea is more common in children with giardiasis than in healthy subjects. Because of the location of the disaccharidases in the intestinal brush border, any condition that damages its morphology (such as severe diarrhea), will result in a detrimental effect on these enzymes, and thus disaccharides absorption.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar results were found by Gendrel and others, who reported that asymptomatic giardiasis does not increase the frequency of lactose intolerance in well-nourished children. 4 Furthermore, Tolboom and others 27 found that lactose malabsorption does not correlate with the presence of giardiasis, but milk intolerance manifested as diarrhea is more common in children with giardiasis than in healthy subjects. Because of the location of the disaccharidases in the intestinal brush border, any condition that damages its morphology (such as severe diarrhea), will result in a detrimental effect on these enzymes, and thus disaccharides absorption.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have reported the potential effects of moderate or asymptomatic giardiasis on nutrient absorption, and thus the effects on the nutritional status of the host. 4,[25][26][27] For instance, de Morais and others found that asymptomatic giardiasis did not affect the intestinal absorption of iron in children with iron deficiency. 25 We have previously found that mild G. intestinalis infection did not affect energy metabolism (energy intake, basal metabolic rate, and total energy expenditure) in children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parasitosis of children with ascaris (Taren et al 1987) and giardia (Tolboom et af. 1987) was shown to increase lactose maldigestion; a more recent study in well nourished African children (Gendrel et al 1992) showed a marginal effect of ascaris and no effect of giardia on lactose digestion. Perhaps the overall nutritional status of children is a more important determinant of the capacity to digest lactose.…”
Section: Secondary Lactase Deficiencymentioning
confidence: 93%
“…Son varios los artículos publicados que apoyan o refutan diferentes relaciones (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Esto se debe a que el peso, la talla y, en general, el estado nutricional de un individuo a lo largo de su vida depende de la compleja interacción de una serie de variables entre las cuales están su propia información genética, patologías que pueden afectar su desarrollo desde la vida intrauterina, el nivel socioeconómico y las conductas alimentarias de la familia y la sociedad a las que pertenece, así como las patologías que retrasan su crecimiento y desarrollo durante la infancia, la niñez y la pubertad, entre las cuales el parasitismo intestinal es tan sólo una (1,12).…”
unclassified